Papilloma inversum – report of two cases - Lewandowski, Bogumił; Leja, Michał; Brodowski, Robert; Gawron, Iwona; Pakla, Paweł (Journal of Stomatology, 2016)
The paper presents the descriptions of two patients with a diagnosis of inverted papilloma, which is uncommon in clinical practice and can cause diagnostic difficulties. The most common place of occurrence is spaces of paranasal sinuses and nasal cavity. The clinical picture is often manifested as maxillary sinusitis. The diagnostic difficulties highlighted in this study stem from lack of specific clinical symptoms, necessitating further imaging and making the diagnostic process longer. In the described cases, the treatment was undertaken after obtaining the result of the histopathological examination. The authors’ observations confirm the need to perform radical surgery due to the high degree of recurrence and a possibility of malignant transformation.